THE IMPACT OF COVID-19 PANDEMIC ON BANKS IN INDONESIA: COMPARATIVE ANALYSIS - Nanang , Rusliana; Dyah , Wardhani; Sri , Sudiarti; Neng Yesi, Susanti (STIE PGRI Dewantara Jombang, 2023)
This study aimed to determine the conditions of the digital transaction sector, financial system stability, financial inclusion, and bank health ratios before and after the COVID-19 pandemic and their impact on digital transactions, financial system stability, financial inclusion, and banking health ratios in Indonesia. The research method used is the descriptive comparative analysis method. The analysis used in this study is the average difference test analysis using the paired samples t-test. The results of the study show that digital transactions during the COVID-19 pandemic did not have a significant impact on reducing electronic money. The COVID-19 pandemic significantly impacted lowering average inflation and interest rates (BI7DRR). Furthermore, the COVID-19 pandemic substantially affected reducing average public savings. However, it did not considerably influence the decrease in the average public loan. The COVID-19 pandemic has significantly reduced the average bank soundness ratio as measured by Return on Assets (ROA) and Loan to Deposit Ratio (LDR).